Platform Merdeka Mengajar terhadap Kompetensi Pedagogik Guru di SMAN 1 Sukaresmi Cipanas - Okpatrioka Okpatrioka; Ginawati Ginawati; Nono Yatno (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
The curriculum changes that occur are a challenge for teachers in implementing them. For this reason, the Ministry of Education and Culture launched the Merdeka Teaching Platform with the aim of helping teachers understand and implement the Merdeka Curriculum. This research aims to determine the use of the Merdeka Mengajar Platform on the pedagogical competence of teachers at SMA Negeri 1 Sukaresmi Cipanas. This research is a type of evaluative research with a quantitative descriptive approach. The sample in this study consisted of 40 people. Data analysis in this research was carried out descriptively. The results of research regarding the use of the Merdeka Mengajar platform on the pedagogical competence of teachers at SMA Negeri 1 Sukaresmi Cipanas, with the percentage of results for the Video Inspiration feature, 78% for the Independent Training feature, 82% for the Evidence of Work feature, 76% for the Student Assessment feature, and 70% for Teaching Tools features, it can be concluded that this platform has played a significant role in supporting the development of teacher pedagogical competence. Overall, this research shows that the Merdeka Mengajar platform has been well utilized by teachers at SMA Negeri 1 Sukaresmi Cipanas. However, there are still several aspects that need to be improved to ensure that all features can be used optimally by all teachers, so that they can maximize their pedagogical competence.